Physical hydrogels prepared from cationically modified pectin with tunable sol-gel phase transition behaviors - Nootcharee Kunkit (2020)
© 2019, © 2019 Taylor & Francis Group, LLC. In this present work, physical hydrogels were prepared by the reaction between pectin and bis (3-aminopropyl) amine (APA) using N-hydroxysuccinimide (NHS) and 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC) as catalysts. These pectin-graft-bis (3-aminopropyl) amine (pec-g-APA) copolymers exhibited the electrostatic induced sol-gel phase transition at the predetermined pH values. Sol-gel phase diagrams demonstrated both lower- and upper- phase boundaries, corresponding to sol-gel phase transition and gel-sol phase transition, respectively, upon varying pH of the system. The phase transition depended on the APA composition as well as the copolymer concentration so that the gelation can be manipulated. The hydrogels were non-cytotoxic and exhibited the potential use for controlled release of gentamicin. Also, the antimicrobial activity of released gentamicin remained unaffected by the hydrogels.